Managing a Rivaroxaban Bleed: Understanding the Difficulties in Acute Reversal of the New Oral Anticoagulants through a Case Report - Nannapaneni, Naveen; Singh, Robby; Mckay, Paulina; Al-Hajeili, Marwan (Case Reports in Hematology, 2014)
With the arrival of a new generation of oral anticoagulants significant burdens associated with warfarin’s use on both the patient and the healthcare system have been alleviated. Nevertheless, a shortfall exists in regard to an agent or protocol for reversal of these new anticoagulants in the setting of an acute bleed. Our case of a patient presenting to the hospital with a vaginal bleed while on rivaroxaban highlights the difficulty in management without a clear protocol or agent for reversal of anticoagulation.